Notes and new species of the halictine genus Megommation Moure (Hymenoptera, Apidae, Augochlorini) - Gonçalves, Rodrigo B.; Santos, Leandro M. (Zootaxa, 2010)
A new species of Megommation, M. amazonicum n. sp., is described and illustrated. An identification key for the two species of this genus is provided. Additionally, the lectotype and paralectotype of Megalopta (Megaloptella) ipomoea Schrottky are designated.